The Effect of Corporate Social Responsibility (CSR) And Company Size on Tax Avoidance (Case Study of Companies in All Sectors Listed on the Indonesia Stock Exchange for the Period 2019-2023) - Ayu Aprina; Tertiarto Wahyudi; Sukanto Sukanto (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to analyze the effect of Corporate Social Responsibility (CSR), Capital Intensity, Gender Diversity, and Company Size on tax avoidance. The main theoretical framework used includes stakeholder theory, legitimacy theory, and Stewardship theory. Secondary data used were obtained from annual reports and sustainability reports of companies listed on the Indonesia Stock Exchange (IDX) during the period 2019-2023. The study population includes all companies listed on the Indonesia Stock Exchange (IDX) during that period, with a purposive sampling technique. The sample consisted of 30 companies with a research period of five years, resulting in a total of 150 observations. The results of the study indicate that CSR and company size affect tax avoidance.